The Dynamics of The National Movement to Indonesian Independence in The 20TH Century - Johan Septian Putra (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2023)
The 20th century was given the nickname as the century of nationalism for Indonesia with national political awareness. Ethical political policies provide opportunities for Indonesian youth to fight for independence. Education was imposed by the Dutch as a significant factor for the development of the Indonesian nation because education could influence and experience the development of thought as the foundation for the birth of the idea of ??nationalism among Indonesian youth. The purpose of this study is to explain the description of the national movement at the beginning of the 20th century and explain the end of the struggle of the national movement at the beginning of the 20th century. The research method of this study is a historical research method with library research and tracing information sources for this study through the internet. The flow or procedural of the historical research method, which includes four stages, namely heuristics, in the form of collecting materials/sources; source criticism in the form of internal-external criticism; interpretation in the form of classifying data and looking for causal law; and explanation in the form of historiography. The results of the research in this study are first, the national movement in Indonesia is a movement of change to elevate the dignity of the Indonesian nation to become a strong and independent country without any intervention from other nations. The establishment of organizations or associations based on anti-imperialist politics and the struggle for independence from the colonialists. The breakthrough of the spirit of nationalism but became the main ideology to get Indonesia's independence. Second, the end of western imperialism against Asian nations, especially parts of Southeast Asia including Indonesia, was defeated by Japan in the mid-20th century, after the Dutch colonialists handed over their power to Japan unconditionally. However, after Japan suffered defeat in World War II, Indonesia's position was the status quo, so the declaration of independence took place without any interference, coercion and pressure from other nations on August 17, 1945.